FACTORS AFFECTING THE LIQUIDITY RISK OF COMMERCIAL BANKS LISTED ON THE INDONESIAN STOCK EXCHANGE - Prasetiyo Hadi Kusumo; Asdi Aprilian Husnadarari Raas; Henny Setyo Lestari (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to identify variables that affect the liquidity risk of the banking sector in Indonesia. Methods: This research method was conducted by collecting data from 41 banking companies over five years (2019-2023), and applying data processing analysis using panel data regression analysis techniques.Results: The results of this study found that CAR, NPL, and SIZE harm liquidity risk (LA), while NPL, SIZE, OIR, and DAR harm liquidity risk (LD). Keywords: liquidity risk, capital adequacy, asset quality, bank size, efficiency, and deposit.